Religion and conflict in modern South Asia - Gould, William, 1973- (Cambridge ; New York : Cambridge University Press, 2012)
"This is an incisive analysis of religious conflict in South Asia, which, the author contends, arises out of the weakness of political and state structures rather than the clash of civilizations"--
"Religion and Conflict in Modern South Asia is one of the first single-author comparisons of different South Asian states around the theme of religious conflict. Based on new research and syntheses of the literature on "communalism",̥ it argues that religious conflict in this region in the modern period was never simply based on sectarian or theological differences or the clash of civilizations. Instead, the book proposes that the connection between religious radicalism and everyday violence relates to the actual (and perceived) weaknesses of political and state structures. For some, religious and ethnic mobilisation has provided a means of protest, where representative institutions failed. For others, it became a method of dealing with an uncertain political and economic future. For many it has no concrete or deliberate function, but has effectively upheld social stability, paternalism and local power, in the face of globalisation and the growing aspirations of the region's most underprivileged citizens"--
Machine generated contents note: 1. Introduction: community and conflict in South Asia; 2. Building spheres of community: 1860s - 1910s; 3. Transforming spheres of community: the post First World War wold; 4. Nationalising spheres of community: anti-colonialism and religious politics; 5. The 1940s, state transformation, community and conflict; 6. National integrity and pluralism, 1947-1967; 7. The decades of transformation: 1970s and 1980s; 8. The resurgence of religious nationalism: 1990 to the present.
Includes bibliographical references (p. 317-336) and index.
Keywords: Social conflict -- South Asia -- History; Social conflict -- Religious aspects -- History; HISTORY / Asia / India & South Asia; South Asia -- Religion